Peran Mediasi Materialisme Pada Pengaruh Harga Diri dan Iklim Etika Terhadap Intensi Korupsi Kader Partai Politik - Hanum, Ifda; Sovitriana, Rilla (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Corruption cases in Indonesia involving members of Dewan Perwakilan Rakyat (DPR) asrepresentatives of society are still occurring. The elected DPR members come from political parties, whichare organizations where people have democracy. Previous studies have shown that self-esteem and ethicalclimate in organizations affect the intensity of corruption. In addition, materialism becomes a mediatorbetween self-esteem and corruption intentions. This research was conducted to determine the intensity ofcorruption in political party cadres from a new perspective. The data obtained from a sample of a politicalparty was then processed using a linear regression technique with the help of IBM version 22 software. Theresults show that self-esteem has an effect of -0.152 (p = 0.002) and ethical climate has an effect of-0.163 (p = 0.001) on corruption intentions. Meanwhile, materialism becomes a partial mediator ofthe influence of self-esteem on corruption intentions. Internal factors within party cadres play an essentialrole in reducing the intensity of corruption. Programs of training activities that can improve the ethical climatein political party organizations are also urgently needed, such as Politik Cerdas Berintegritas Terpadu (PCBTerpadu) organized by Komisi Pemberantasan Korupsi (KPK) together with political parties to realizeIndonesian politics with integrity.